Proposal of an Optimized Airfoil Geometry for Vertical-Axis Wind Turbine Applications - Andrés Meana-Fernández; Lorena Díaz-Artos; Jesús Manuel Fernández Oro; Sandra Velarde-Suárez (Proceedings, 2018)
In this work, an airfoil geometry optimized for vertical-axis wind turbine applications is presented. Different airfoil shapes have been analyzed with JavaFoil, a panel method software. Then, the results from the analysis have been used to optimize the performance of the proposed airfoil shape (UO-17-LDA). This airfoil presents a high lift-to-drag ratio and a delayed stall angle with respect to the original FX-63-137 airfoil, making it suitable for vertical-axis wind turbine applications. The practicality of JavaFoil for the comparison of different airfoil geometries has been verified, as it is capable of obtaining results for a wide number of flow conditions in small computational times and with a user-friendly interface. Nevertheless, the results diverge from the actual solution for high angles of attack (beyond stall).